PERUBAHAN PENUTUPAN LAHAN HUTAN DI CAGAR ALAM DOLOK SIBUALBUALI TAHUN 2006 DENGAN 2013 - Windy Sahraeni Batubara; Anita Zaitunah; Muhdi Muhdi (Program studi Kehutanan USU, 2016)
Nature Reserve area Dolok Sibual-Buali government administratively located in the village Banyan, Marancar and Tapus, District Sipirok Batang Toru and Mulberry South Tapanuli. Conditions Nature Reserve is still intact and is a source of water for the surrounding area. The purpose of this study was to determine the changes in land cover and determine the condition land cover there in 2006 and 2013 by using the interpretation of Landsat ETM 7 and 8. Landsat TM image analysis and classification change detection method using Arcview Gis 3.3 and ERDAS IMAGINE 8.5. Image analysis were performed, land cover in the Nature Dolok Sibual-Buali classified into 5 classes of land cover namely primary dry forest, secondary dry forest, scrub, vacant land, water bodies and not identified (clouds and cloud shadows). The results obtained by the classification of the primary dry forest is 68.5 ha changed into a secondary dry forest and 11.8 ha to Body Air.Pada secondary dry forest area of ​​583.28 changes ha become better forest and 30.61 ha turned into Shrublands., 74 ha.Sedangkan on bushes changed into the body area of ​​3.42 ha of water. Keyword : Land coverage change, Dolok Sibualbuali Nature Reserve.